The transmitted and reflected waves due to the incidence of a forced wave on a junction. Issue 1 (March 2016) - Davy, John L; Irwin, Alexandra L
The airborne sound transmission through a plate below its critical frequency is dominated by forced waves even though the plate vibration is dominated by freely propagating waves. This article studies whether the transmission of the two wave types is different at a junction. It is shown in this article that it is not possible to separately calculate in a meaningful way the intensity of a forced incidence wave and its freely propagating reflected wave in the medium from which incidence occurs because the cross terms in the intensity calculation for the combined waves, which vanish when the incident wave is freely propagating, do not vanish when the incident wave is forced. This means that it is not possible to define a transmission factor for forced incident waves. Thus, the transmitted intensity must be calculated as a function of the mean square wave amplitude of the forced wave.